The Psilotreta Banks, 1899 of the Dabie Mountains, east central China, with descriptions of two new species (Insecta: Trichoptera: Odontoceridae) - Qiu, Shuang; Yan, Yun-jun (European Journal of Taxonomy, 2020)
The authors collected caddisflies in the Dabie Mountains in 2014 and 2015. Three species of Psilotreta Banks, 1899 were found: Psilotreta daidalos Malicky, 2000, P. furcata sp. nov., and P. brevispinosa sp. nov. The species were collected by light sheet traps or hand nets near streams in mountainous forests. All the species are described and illustrated, and the species groups to which they belong are discussed. Some variation within P. daidalos is described and the species is newly recorded from the Anhui and Hubei Provinces.